Impact of the USDA Fresh Fruit & Vegetable Program on Children's Consumption and Other Related Behaviors - Hoffman, Lainee; Reinhold, Kevin; Fisher, Stephen; Mabrey, Stephanie; Ross, April; Dickinson, Judy; Wieseman, Laurelyn (My University, 2012)
This study investigated the impact of the 2009-10 Fresh Fruit and Vegetable Program on intake and other behaviors related to fruit and vegetable consumption among Wisconsin 4th- and 5th-grade students.
Color poster with text, images, and graphs.
Keywords: Posters; Fresh Fruit and Vegetable Program (Wis.); School children--Wisconsin--Attitudes